Introduction to HTML and CSS - Huddleston, Rob (Apress, 2018)
"Get started on the basics of creating websites with HTML and CSS ... Key topics to be covered are the foundational concepts behind how the web works and the advantages to coding your own site versus using online templates. Then, you will be introduced to the HTML tags used on the vast majority of sites and learn how to properly structure sites to make them easy to design, easy to maintain, and flexible enough to view on all screens (also known as responsive design). Finally, CSS will be introduced to show you how to create beautiful designs."--Resource description page